Forte en Verdedigingswerke op die Kaapse Oosgrens 1806-1836 - Bezuidenhoud, P.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
This article deals with fortresses and defensive works on the Cape eastern border during the period 1806 to 1836 describing not only the appearance and floorplans of the fortresses but what gave rise to their coming into existence and what role they fulfilled in the historical events of the time.